Glass transition of random heteropolymers: A molecular dynamics simulation study in melt, in water, and in vacuum. (16th January 2023) - Jin, Tianyi; Hilburg, Shayna L.; Alexander-Katz, Alfredo
Abstract: Random heteropolymers (RHPs) have a long history of being studied as toy models for protein folding. Previous computational studies applied statistical mechanics or coarse-grained methods to investigate the RHP phase transition; here, we use atomistic molecular dynamics (MD) simulations to explore the factors affecting the glass transition temperature (Tg ) and the mobility of a complex class of RHPs. Our RHPs consist of four methyl methacrylate-based monomers with side chains mimicking different classes of amino acids. We explore the dynamical features in the RHP melts with random sequence mixtures and show that instead of a sharp pseudo-second-order glass transition, as for PMMA, RHPs with low ionic contents show a soft and gradual transition and those with increased content of ionic monomers show a sharp transition. Meanwhile, the configurational entropy of the backbone dihedral angle decreases suddenly in both PMMA and RHPs as a common signature of the glass transition. The dynamical spatial heterogeneity during the glass transition is related to both the chemical structure of the monomers and their positions along the chain. Moreover, chain mobility depends on the content of ionic monomers and types of counterions. The comparison with the single-chain nanoparticles (SCNPs) in water and in vacuum shows "breathing dynamics" with higher mobility. Our work characterizes the physicochemical properties of the RHP melts as a group of emerging bio-inspired polymer materials. Graphical abstract: Image 1 Highlights: Random heteropolymers show distinct glass transition with an interplay of MMA backbone, steric side chain, and ionic content. The configurational entropy of backbone dihedral angle decreases suddenly as a common signature of the glass transition. The dynamical spatial heterogeneity is related to the chemical structure of the monomers and their positions along the chain. Single-chain nanoparticles (SCNPs) in water and in vacuum shows "breathing dynamics" with higher mobility.